Instrumentation Development for In Situ40Ar/39Ar Planetary Geochronology. Issue 3 (30th April 2017) - Morgan, Leah E.; Munk, Madicken; Davidheiser‐Kroll, Brett; Warner, Nicholas H.; Gupta, Sanjeev; Slaybaugh, Rachel; Harkness, Patrick; Mark, Darren F.
Abstract : The chronology of the Solar System, particularly the timing of formation of extra‐terrestrial bodies and their features, is an outstanding problem in planetary science. Although various chronological methods for in situ geochronology have been proposed (e.g., Rb‐Sr, K‐Ar), and even applied (K‐Ar), the reliability, accuracy, and applicability of the 40 Ar/ 39 Ar method makes it by far the most desirable chronometer for dating extra‐terrestrial bodies. The method however relies on the neutron irradiation of samples, and thus a neutron source. Herein, we discuss the challenges and feasibility of deploying a passive neutron source to planetary surfaces for the in situ application of the 40 Ar/ 39 Ar chronometer. Requirements in generating and shielding neutrons, as well as analysing samples are described, along with an exploration of limitations such as mass, power and cost. Two potential solutions for the in situ extra‐terrestrial deployment of the 40 Ar/ 39 Ar method are presented. Although this represents a challenging task, developing the technology to apply the 40 Ar/ 39 Ar method on planetary surfaces would represent a major advance towards constraining the timescale of solar system formation and evolution. Key Points: The extra‐terrestrial deployment of the 40 Ar/ 39 Ar geochronological method using 252 Cf as a neutron source is explored. Critical issues are discussed: neutron formation, sample irradiation, sample analysis and neutron shielding. This technology could be used to calibrate the crater‐counting method of dating extra‐terrestrial surfaces.